Penerapan Media Handout Digital terhadap Hasil Belajar Membuat Gambar Bagian dan Bentuk Busana Siswa Kelas X Tata Busana SMK Dharma Wanita Gresik - Alfi Wardatus Saniyyah; Marniati Marniati (Journal on Education, 2023)
This study describes the application of digital handout media to the basic competencies of make drawing parts and forms of clothing on the learning outcomes of class X students of fashion at SMK Dharma Wanita Gresik. Digital handouts are one of the facilities that contain a summary of the material presented by educators which are presented in network form and can be accessed via gadgets, laptops, and computers. The purpose of this study was to find out student activities, how students responded, and student learning outcomes with the application of digital handout media in learning to make pictures of parts and forms of clothing. This research method uses descriptive quantitative research using a one-shot case study research design with 10 students in class X fashion design at SMK Dharma Wanita Gresik as the research subjects. The results of this study were that student activity in using digital handout media obtained an average score of 90% at each meeting and 93% as the highest score, student responses to digital handout media obtained a simultaneous percentage of 89.9% categorized as very good, student learning outcomes after being applied digital handout media obtains a classical completeness percentage of 100% with the criterion of 10 students being complete in learning. This study concluded that the application of digital handout media can make students more enthusiastic and active in learning to make images of parts and forms of clothing at SMK Dharma Wanita Gresik and able complete students learning outcomes with very good and positive responses from students.